Experimental study and anatomo-histopathological, clinico-pathological and behavioral characterization of chytridiomycosis in Lithobates vibicarius in the highlands of Costa Rica - Barboza, Gilberth José Alvarado (2019)
The global phenomenon of the amphibian declines has been well described and documented. There is a consensus made by the scientific community that this event occurred simultaneously in many countries around the world. What makes the nature of this phenomenon distinctive is that it occurs in protected and pristine locations. In Costa Rica there is a group of seven species of frogs with a low number of individuals in their populations and restricted to a very small geographic area; amongst them Craugastor ranoides, Craugastor taurus, Agalychnis lemur, Agalychnis annae, Ptychohyla legleri and Incilius holdridgei. Another species that belongs to this group is Lithobates vibicarius, which is endemic from the highlands of Costa Rica and western of Panamá. During the 90\'s it was presumed to be extinct and this was attributed to Batrachochytrium dendrobatidis (Bd) , but recently started to recolonize and established relict populations in two sites of Costa Rica. Nowadays, a relict population seems to be well established at the Juan Castro Blanco National Park (JCBNP), since it appears to have a high number of adults, juveniles and tadpoles over its reproductive seasons and in appearance seems to be a healthy population. All these characteristics facilitate the use of individuals of this species population to obtain biological samples for different Bd-susceptibility evaluations, and innovative analysis to obtain robust information on how to implement a management program. Before considering a translocation program or the reintroduction of the species Lithobates vibicarius, it is necessary to verify its resistance and survival when exposed to Bd. Thus, we use one of the isolated strains in one of the most potential sites for the reestablishment of this species population. The objective of this study was built on the premise that many amphibian species from Costa Rica had population declines caused by chytridiomycosis. Thus, through anatomo-histopathological, clinico-pathological and behavioral studies, we seek to investigate the different phases of Bd infection in the species of interest. We established adequate facilities and standardized operating procedures in order to ensure animal welfare and to obtain high quality generated data during the process of experimental infection. The results obtained showed that L. vibicarius was competent to resolve the clinical signs presented in a two week period and within 8 weeks, more than 80% of the animals had eliminated the Bd, as suggested by histopathologic and molecular analysis results. There are no indications of anatomo-pathological, hematologic or behavioral alterations directly associated with the experimental process of infection. Based on our results, Bd infection in L. vibicarius is self-limiting with low morbidity and no mortality. Thus, the results presented here suggest that it is not possible to attribute the decline of these species to chytridiomycosis based only on the diagnoses of the infection, despite the mortality observed in wild in the 90s. Complementary studies are needed to uncover the various aspects related to in situ mortalities.